2009
DOI: 10.1098/rsif.2009.0161.focus
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and inflammation response after nanoparticle exposure: differences between human lung cell monocultures and an advanced three-dimensional model of the human epithelial airways

Abstract: 4Kantonsschule Frauenfeld, Frauenfeld, SwitzerlandCombustion-derived and manufactured nanoparticles (NPs) are known to provoke oxidative stress and inflammatory responses in human lung cells; therefore, they play an important role during the development of adverse health effects. As the lungs are composed of more than 40 different cell types, it is of particular interest to perform toxicological studies with co-cultures systems, rather than with monocultures of only one cell type, to gain a better understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
117
1
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 71 publications
13
117
1
3
Order By: Relevance
“…In contrast, however, a study in which different nanofiber (single-walled CNTs (SWCNTs)) and nano-objects (titanium dioxide (TiO 2 )) were assessed for their ability to stimulate pro-inflammatory cytokine/chemokine markers, as well as affect total antioxidant capacity (TAC) within the triple cell coculture. 30 It was reported that the in vitro model elicited a significant decrease (p < 0.05) in the TAC following SWCNTs exposure, while TiO 2 caused a significant increase (p < 0.05) in TAC of the triple cell coculture. Similar results were found for the pro-inflammatory cytokine TNF-α and chemokine IL-8, in contrast to the findings of ref 29.…”
Section: ' Results and Discussionmentioning
confidence: 93%
“…In contrast, however, a study in which different nanofiber (single-walled CNTs (SWCNTs)) and nano-objects (titanium dioxide (TiO 2 )) were assessed for their ability to stimulate pro-inflammatory cytokine/chemokine markers, as well as affect total antioxidant capacity (TAC) within the triple cell coculture. 30 It was reported that the in vitro model elicited a significant decrease (p < 0.05) in the TAC following SWCNTs exposure, while TiO 2 caused a significant increase (p < 0.05) in TAC of the triple cell coculture. Similar results were found for the pro-inflammatory cytokine TNF-α and chemokine IL-8, in contrast to the findings of ref 29.…”
Section: ' Results and Discussionmentioning
confidence: 93%
“…However, it is likely that both the perturbation of epithelial cell barrier integrity and direct activation of DC are important in the elicitation of a proallergic innate immune response to 'environmental danger signals' since interdigitating DC are after all capable of sampling ambient PM via the tight junctions of pulmonary epithelia [35,52,[61][62][63][64] . It is also important to point out that it has been shown that relatively larger macromolecules (for example respirable coarse/fine ambient PM) may not overcome the integrity of the bronchial epithelial cell barrier and instead may be deposited and accumulated on the luminal surface of the epithelia where DC residing essentially underneath the epithelial barrier may directly capture those particles without affecting the integrity of the epithelia at all [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Since the lung is expected to be one antioxidant capacity and the cytokine excretion 205 . It can therefore be stated that the interplay between different cell types significantly modulates the oxidative stress levels and the inflammatory response, which are both known to be affected by NP exposure.…”
Section: Effect Of Intercellular Communication On Np Toxicitymentioning
confidence: 99%